An Epistemic Argument in Support of Liberal Neutrality - Garreta Leclercq, Mariano (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2009)
My aim in the present paper is to develop a new kind of argument in support of the ideal of liberal neutrality. This argument combines some basic moral principles with a thesis about the relationship between the correct standards of justification for a belief/action and certain contextual factors. The idea is that the level of importance of what is at stake in a specific context of action determines how demanding the correct standards to justify an action based on a specific set of beliefs ought to be. In certain exceptional contexts –where the seriousness of harm in case of mistake and the level of an agent’s responsibility for the outcome of his action are specially high– a very small probability of making a mistake should be recognized as a good reason to avoid to act based on beliefs that we nonetheless affirm with a high degree of confidence and that actually justify our action in other contexts. The further steps of the argument consist in probing 1) that the fundamental state’s policies are such a case of exceptional context, 2) that perfectionist policies are the type of actions we should avoid, and 3) that policies that satisfy neutral standards of justification are not affected by the reasons which lead to reject perfectionist policies.